Aegla platensis Schmitt, 1942 (Decapoda: Anomura) um predador de imaturos de Simuliidae (Diptera: Culicomorpha) Aegla platensis Schmitt, 1942 (Decapoda: Anomura) a predator of Simuliidae imature stages (Diptera: Culicomorpha) - Sandra Tonetti Magni; Victor Py-Daniel (Universidade de São Paulo, 1989)
Observações de campo e de laboratório evidenciaram, pela primeira vez, a predação preferencial, de larvas e pupas de simulídeos pelo crustáceo. Aegla platensis Schmitt, 1942. Foram feitas observações de campo e coletas no arroio Carpintaria, Município de Dois Irmãos, Rio Grande do Sul, Brasil. É ressaltada a possibilidade de ser usado esse caranguejo em manejo integrado no controle de simulídeos. For the first time, preferential predation of larvae and pupae of Simuliidae by the crustacean, Aegla platensis Schmitt, 1942, was observed in the field and in the laboratory. Field observations and collections were done in the Carpintaria stream, Dois Irmãos, Country Rio Grande do Sul, Brazil. The possibility of using this freshwater crab in an integrated control of Simuliidae is discussed.